2016
DOI: 10.1007/s12529-016-9593-4
|View full text |Cite
|
Sign up to set email alerts
|

The Validity and Reliability of the Korean Version of the Stigma Scale for Chronic Illness 8-Items (SSCI-8) in Patients with Neurological Disorders

Abstract: This study shows that the Korean SSCI-8 is a unidimensional model, even though it includes items of both enacted and internalized stigma. It is both reliable and valid for assessing stigma among Korean patients with neurological disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
3
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
3
3
0
3
Order By: Relevance
“…In terms of reliability, the study results indicated that SSCI-7 has desirable internal consistency both in total scale and the subscales. For the total scale, it was consistent with the results of the original study (Molina et al, 2013) and the study on Korean patients with neurological disorders (Yoo et al, 2017). Moreover, the AVE index above 0.5 for the total scale and each subscale demonstrated that each item could contribute to a high amount of variances of the scale (Hair et al, 2010).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In terms of reliability, the study results indicated that SSCI-7 has desirable internal consistency both in total scale and the subscales. For the total scale, it was consistent with the results of the original study (Molina et al, 2013) and the study on Korean patients with neurological disorders (Yoo et al, 2017). Moreover, the AVE index above 0.5 for the total scale and each subscale demonstrated that each item could contribute to a high amount of variances of the scale (Hair et al, 2010).…”
Section: Discussionsupporting
confidence: 83%
“…In contrary, the original study by Molina et al, using item response theory indicated unidimensionality of the scale among patients with different neurological disorders (Molina et al, 2013). A study from Korea aiming to validate the scale among patients with neurological disorders also yielded a unidimensional factor structure encompassing both enacted and internalized stigma (Yoo et al, 2017). This disparity suggests that the stigmatism of different conditions might entail dissimilar structures, as it contains differences in terms of impact (Else-Quest et al, 2009).…”
Section: Discussionmentioning
confidence: 95%
“…The overall Cronbach α reliability would not be improved by removing any item (change ies. 9,23 Combining the internal reliability found in the present and previous studies, the pooled Cronbach α is 0.89 (95% CIs, 0.88-0.90). Molina et al 9 and Yoo et al 23 do not provide factor loadings from CFA for comparison with ours.…”
Section: Internal Reliabilitysupporting
confidence: 66%
“…9,23 Combining the internal reliability found in the present and previous studies, the pooled Cronbach α is 0.89 (95% CIs, 0.88-0.90). Molina et al 9 and Yoo et al 23 do not provide factor loadings from CFA for comparison with ours. However, the results of the three studies converge on the existence of a unidimensional structure underlying the stigma construct as evaluated using the SSCI-8.…”
Section: Internal Reliabilitysupporting
confidence: 66%
“…Mindez szükségessé teszi a krónikus megbetegedések kapcsán a stigmatizáció felismerését és felmérését. Jelenleg két rövid stigmatizáció-kérdőív áll rendelkezésünkre, a Krónikus Betegségekben Anticipált Stigma Skála (Chronic Illness Anticipated Stigma Scale -CIASS; [3]), valamint a 8 tételes Stigmatizáció Krónikus Betegségekben Kérdőív (Stigma Scale for Chronic Illness -8, SSCI-8; [10][11][12]). A CIASS [3] a stigmatizáció felmérésének 12 tételes, megbízható mérőeszköze, azonban csupán az egyik stigmatizációfaktor, az ún.…”
unclassified